BWM HONAY SEJAHTERA: SOLUSI PERMODALAN UMKM TERDAMPAK COVID-19 DI KOTA JAYAPURA - Ahmad Havid Jakiyudin; Natasya Aula Husain; Muhammad Yusuf (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
Capital is the main problem for MSMEs to survive during pandemic covid-19. MSMEs actors generally only depend on bank sector, cooperative, and moneylender to overcome these problem. The purpose of this research is to provide the best solutions for MSMEs actors in Jayapura City affected by Covid-19 who have difficulty accessing the capital. This study used a qualitative descriptive method with studi case approached. Data collection through library research and field research from participatory observation, in-depth interviews, and documentation, data analysis techniques using Miles and Huberman techniques in the form of: reducing, presenting data and drawing conclusions. The results of the research conducted indicate that BWM Honay Sejahtera Papua can be an alternative for micro-scale business actors in Jayapura City who have difficulty finding capital without interest and collateral. Capital assistance is given to micro-scale entrepreneurs scattered in Jayapura City such as street vendors, mobile cake sellers, areca nut sellers, etc. BWM Honay Sejahtera Papua provides a capital loan with a mentoring program so that it will form productive MSMEs.